2020
DOI: 10.1051/radiopro/2020082
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from and perspectives for healthcare student volunteer activities after the Fukushima disaster

Abstract: Healthcare students are key resources after nuclear disasters. Healthcare students at Fukushima Medical University volunteered after the Great East Japan Earthquake and Fukushima nuclear accident. At the time of the disaster, healthcare students, who were in a position between medical and non-medical people, listened to the various concerns and worries of victims. Specifically, they established the Fukushima WILL – a disaster medical club. These activities have continued for about 10 years after the Fukushima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This theme included articles that investigated how knowledge of policies and participation in youth forums empower youth to engage in DRR activities. The fourth theme of education-community partnerships (n = 9; Chen & Adefila, 2020; Cox et al, 2019;Fernandez & Shaw, 2015;Kawashima et al, 2021;Nakano, Suwa, Gautam, & Yamori, 2020;Osofsky et al, 2018;Petterson et al, 2019;Richards, Novak, & Davis, 2009;Shillingford, Williams, & Allen, 2020) included articles that discussed the role of educational institutions including universities and how YYAs' involvement in service-learning initiatives can lead to experiences of community and youth mutual support and knowledge sharing. One study under this theme described how youth from the Philippines participated in science clubs that were able to provide immediate help with disaster search and rescue.…”
Section: Resultsmentioning
confidence: 99%
“…This theme included articles that investigated how knowledge of policies and participation in youth forums empower youth to engage in DRR activities. The fourth theme of education-community partnerships (n = 9; Chen & Adefila, 2020; Cox et al, 2019;Fernandez & Shaw, 2015;Kawashima et al, 2021;Nakano, Suwa, Gautam, & Yamori, 2020;Osofsky et al, 2018;Petterson et al, 2019;Richards, Novak, & Davis, 2009;Shillingford, Williams, & Allen, 2020) included articles that discussed the role of educational institutions including universities and how YYAs' involvement in service-learning initiatives can lead to experiences of community and youth mutual support and knowledge sharing. One study under this theme described how youth from the Philippines participated in science clubs that were able to provide immediate help with disaster search and rescue.…”
Section: Resultsmentioning
confidence: 99%
“…But this does not mean that their consequences on RP can be totally disregarded: difficulties with online system, with the new working management, delays, lack of interaction with co-workers and the rest of the communities, not to mention the psychological aspects (stress) have been reported repeatedly. Indeed, previous studies have shown that health crises can cause anxiety in the acute phase (Kawashima et al, 2020) and specifically that confinement measures and stay-at-home orders implemented in Japan after the Fukushima nuclear accident have been associated with higher levels of changes in mental health (Sawano et al, 2020), which can last for years (Hori, 2020). The evolution of the situation might be worthwhile to investigate by the IRPA Young Generation Network and national networks.…”
Section: Discussionmentioning
confidence: 99%
“…A key group of people who may serve as facilitators between the authorities and experts and the affected population are healthcare professionals (Kawashima et al, 2020;Ozaki et al, 2020). As such, the SI-WG proposed to create a document intended for medical care professionals with two objectives: to provide answers to questions that patients could ask their healthcare professionals, and to provide answers to the healthcare professionals' own questions.…”
Section: Healthcare Professional Working Groupmentioning
confidence: 99%